2014
DOI: 10.1080/17550874.2014.960173
|View full text |Cite
|
Sign up to set email alerts
|

Shrubs as foundation species in a high tropical alpine ecosystem: a multi-scale analysis of plant spatial interactions

Abstract: Background: Studies on plant-plant interactions in alpine ecosystems show a strong bias for temperate vs. tropical latitudes and pay limited attention to the implications of biophysical heterogeneity beyond the local plant scale. Aims: To evaluate the effects of a dominant shrub (Hypericum laricifolium) on community organisation, integrating multiple scales of analysis, in a high Andean páramo in Venezuela. Methods: We compared plant cover, species richness and Shannon diversity between plots placed under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 76 publications
(76 reference statements)
3
28
0
1
Order By: Relevance
“…; Gómez‐Aparicio ; Cáceres et al. ), as well as research exploring the potential of some species to act as nurses in old‐fields where forests are reestablishing (Holl et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Gómez‐Aparicio ; Cáceres et al. ), as well as research exploring the potential of some species to act as nurses in old‐fields where forests are reestablishing (Holl et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Cáceres et al. ). However, in the more mesic conditions of tropical mountain forests this issue remains largely unexplored.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, Sklenar () reported that high elevation (>4600 m) plant species tend to grow associated with rock outcrops in the Ecuadorian super‐paramo, while Cáceres et al . () showed a positive correlation between large shrubs and rock cover in half of their study sites in the Venezuelan Andes.…”
Section: Percent Ground Coverage Of Plant Species Colonizing Rock Outmentioning
confidence: 93%
“…In harsh systems, such as tropical alpine environments, these processes constitute basic elements of vegetation processes [4]. Previous studies highlighted that facilitative interactions are more common than competitive ones in conditions of high abiotic stress (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they demonstrated how these nurse-induced microhabitat modifications positively influenced the physiological parameters of facilitated species [23]. However, other authors found contrasting results on the effect of ecosystem engineers on species richness at a wide scale [4]. One limitation in our current understanding of the impact of engineer species on the richness of plant communities is that most of the existing works analysed different ecosystem engineers separately, or were located in areas dominated by a single nurse species.…”
Section: Introductionmentioning
confidence: 99%